2003
DOI: 10.1097/01.tp.0000066806.10029.7a
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with humanized monoclonal antibodies against CD80 and CD86 combined with sirolimus prolongs renal allograft survival in cynomolgus monkeys1

Abstract: Sirolimus can be successfully combined with humanized mAb against CD80 and CD86. Induction with a short course of mAb is effective in prolonging allograft survival in combination with sirolimus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 34 publications
(44 reference statements)
1
24
0
Order By: Relevance
“…There have been attempts to utilize NPs that combine antigen and immunesuppressive agents such as rapamycin to alter DC phenotype in vivo and potentially induce tolerance [5,6,9]. Rapamycin has been known for over two decades to have 'tolerogenic' effects when combined with antigen [91,92] and the adoptive transfer of rapamycin-treated DCs can promote the long-term survival of skin grafts in rodent transplant recipients [93]. In the context of NPs, Haddadi and colleagues showed that rapamycin-loaded PLGA NPs preferentially bound to DCs and induced an immature 'tolerogenic' phenotype [61].…”
Section: Np Development For Tolerancementioning
confidence: 99%
“…There have been attempts to utilize NPs that combine antigen and immunesuppressive agents such as rapamycin to alter DC phenotype in vivo and potentially induce tolerance [5,6,9]. Rapamycin has been known for over two decades to have 'tolerogenic' effects when combined with antigen [91,92] and the adoptive transfer of rapamycin-treated DCs can promote the long-term survival of skin grafts in rodent transplant recipients [93]. In the context of NPs, Haddadi and colleagues showed that rapamycin-loaded PLGA NPs preferentially bound to DCs and induced an immature 'tolerogenic' phenotype [61].…”
Section: Np Development For Tolerancementioning
confidence: 99%
“…Prevention of costimulation can result in clonal anergy (Baliga et al 1994). Co-stimulatory blockade has been shown to prolong allograft survival in different transplant models (Adams et al 2002;Birsan et al 2003;Kirk et al 1999). …”
Section: Co-stimulation Blockade and Transplantationmentioning
confidence: 98%
“…Early work to study blockade of the CD28 pathway involved monoclonal antibodies against the B7 ligands CD80 and CD86. Three groups showed prolongation of renal allograft survival using the antibodies 1F1 and 3D1 either alone or in combination with other immunosuppressants (Hausen et al 2001;Kirk et al 2001;Montgomery et al 2002b;Birsan et al 2003). Another group used different clones, B7-24 and 1G10, in rhesus skin and renal transplant models with modest success (Ossevoort et al 1998a,b).…”
Section: Costimulation Blockadementioning
confidence: 99%